Smart System Pendeteksi Keberadaan Narapidana di Lapas Kabupaten Kotawaringin Timur - Riyadi, Slamet; Bachtiar, Lukman; Yunita, Selviana (Generation Journal, 2022)
– The problems regarding prisons are almost endless. The government should pay attention to this. The problems that arise today, almost all correctional institutions in Indonesia exceed (over) capacity, including those in the East Kotawaringin district . Indoor Positioning System IPS is a technology that can be used to locate people or objects in a building, usually through a mobile device such as a smartphone or tablet. Although this technology is newer than GPS, services utilizing IPS are quickly gaining ground in indoor locations such as shopping malls, hospitals, airports and other indoor venues. By utilizing an iBeacon mounted on a prisoner's wristband, the iBeacon will always transmit a signal that can be picked up by the receiver. Devices that can become receivers are bluetooth repeaters (signal boosters) and prison officers' android phones. To be able to know the estimated position of the receiver on the iBeacon, a map is needed locally, which is to determine a certain location, then map it in the form of coordinates. By placing several iBeacons at certain coordinates, it can be used to determine the estimated position of the receiver to the iBeacon.